2017
DOI: 10.1088/1361-6528/aa565a
|View full text |Cite
|
Sign up to set email alerts
|

Stacking sequence dependent photo-electrocatalytic performance of CVD grown MoS2/graphene van der Waals solids

Abstract: New layered solids by the combinatorial stacking of different atomic layers are emanating as novel candidates for energy efficient devices. Here, sequentially stacked single layer graphene-molybdenum disulfide (MoS) van der Waals (vdW) solids are demonstrated for their efficacy in the catalysis of hydrogen evolution reaction (HER), and importance of their stacking order in tuning the photo-electrocatalytic (PEC) efficiency is unraveled. Single layer graphene and a few layered MoS stacked vdW solids based trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 29 publications
2
44
0
Order By: Relevance
“…The vdWs' heterostructures from the individual layers were formed by (PMMA-assisted wet transfer method (Fig. 1a), as discussed in the experimental section [33]. The transferred materials are abbreviated as G (graphene), MS (MoS 2 ), and GMS (graphene-MoS 2 ) throughout the article.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vdWs' heterostructures from the individual layers were formed by (PMMA-assisted wet transfer method (Fig. 1a), as discussed in the experimental section [33]. The transferred materials are abbreviated as G (graphene), MS (MoS 2 ), and GMS (graphene-MoS 2 ) throughout the article.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, such interfacing is found to be resulting in new solids of interesting electronic, optical, and electrochemical properties [30][31][32]. It is shown that even pristine graphene surfaces become electrochemically active while forming vdWs structures with MoS 2 and hBN [33,34]. Furthermore, vdWs structures of graphene with MoS 2 monolayers (MS) were found to provide enhanced hydrogen evolution catalytic activity compared with bare MS along with the enhanced stability even in harsh acid conditions and the interfacial charge transfer from graphene to MS was also established [35].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…S7(c), ESI †) under dark and light conditions. 64 In the dark, the R ct is calculated to be lower for MSTB (102 U) as compared to those of the pristine TB (527 U) and MS (132 U). Interestingly, aer the Pt NP decoration, the R ct dramatically reduces to 36 U, 33 U and 27 U for PMS, PTB, and PMSTB, respectively, in the dark.…”
Section: Hydrogen Evolution Reaction (Her) Studymentioning
confidence: 97%
“…In addition, trapped in a cage of limited electronic conductivity, it is needed to assemble MoS 2 with conductive partners (such as graphene (GR)) to overcome this limitation . Various MoS 2 /GR composites have been developed recently (such as MoS 2 /GR hybrid, MoS 2 /N‐doped GR, and 3D MoS 2 /GR), while these composites are not well controlled in structure with the limited interface contact area between the dozens‐layered MoS 2 sheets and stacked GR sheets, failing to achieve the promising effects observed in single‐layered stacks …”
Section: Introductionmentioning
confidence: 99%
“…[9,10] Various MoS 2 /GR composites have been developed recently (such as MoS 2 /GR hybrid, [11] MoS 2 /N-doped GR, [12,13] and 3D MoS 2 /GR [14,15] ), while these composites are not well controlled in structure with the limited interface contact area between the dozens-layered MoS 2 sheets and stacked GR sheets, [16] failing to achieve the promising effects observed in single-layered stacks. [17,18] Very recently, 2D van der Waals (vdW) heterostructure assembled by stacking MoS 2 and GR layers in hetero-layered architectures (MoS 2 /GR heterostructure) is proposed as a promising electrode material for LIBs and other metal ion batteries. [19][20][21][22][23] In comparison with the reported MoS 2 /GR composites, the large accessible surface of GR can ensure high MoS 2 loading in MoS 2 /GR heterostructure while keeping MoS 2 effectively exposed, which is critical for electrochemical applications.…”
Section: Introductionmentioning
confidence: 99%